Studi Perbandingan Kepuasan Kerja dan Komitmen Organisasi antara Dosen dan Non Dosen pada STT Multimedia Cendikia Abditama - , Muslim Jayadi, Dra. Anita Lestari, MSi. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research is to analyze the comparison of Job Satisfaction and Organizational Commitment between lecturer and non lecturer in STT Multimedia Cendekia Abditama, Tangerang. 30 respondens from 37 employees were chosen for this research. The factors analyzed within Job Satisfaction scoring is done through the five dimensions, the work it self, wage, promotion, job environment condition, supervision, and co-worker is done through the employeeâs response to the questions with using ordinal scale. Organizational Commitment scoring is done through three dimensions, affective, continuance and normative commitment, the employeeâs response to questions regarding their commitment to the organization. Data is then analyzed using t-test, f-test and descriptive analysis. The result of the analysis shows that Job Satisfaction of lecturer is not different with Job Satisfaction of non lecturer. Organizational Commitment of lecturer is different with Organizational Commitment of non lecture